(3GdGYJeGO aj TQM GdYeOI aj GdGYJbGOs - (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf , J (B710 (3g` s; (3MGaX GdOjf CHh GdHQcGJ YHO Gddg Hf CMeO Hf eMehO GdfSaj,J (B710 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJYGdi HceGd UeOjJg Yf GdMdhd hGdGJMGO bGd ehdGfG GHh GdHQcGJ YHO Gddg Hf CMeO Hf eMehO GdfSai deG QCjJ Gdgee eG jdI Edi GdYeOi GdJi SfaJgG ai HjGf YbjOI Ggd GdSfI hGdLeGYI s
(3BNQgG (B:s
(3bjd dGjaVd GMOkG HYO GdUMGHI GdG HGdYde hGdJbhi GdG GhdGO aGWeI aEfge jaVdhf Ydi GhdGO CHj HcQ hYeQ hYKeGf dbQHge ef QShd Gddg Udi Gddg Ydjg hSde hdCfge GdYJQI GdWGgQg hGdPQjI GdWjHI GdPjf GPgH Gddg Yfge GdQLS hWgQge JWgjQkG s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B119s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds